Competency standards for youth development work in the Caribbean. Level III (CYPCC GeorgetownGY, 2012)
Comprises a package made up of a collection of units of competency that cover the full range of work activities within Youth Development Work at the supervised, supervisory and management levels; developed in accordance with the Caribbean Association of National Training Agencies (CANTA) guidelines and with reference to PAULO NTO (UK) Professional and National Occupational Standards for Youth Work (Feb. 2008) Units of Competency, and other material from across the Commonwealth. Provides the basic building blocks for work-based training programmes. Includes List of 30 Units of Competency according to Code YDWCYP0263 to YDWCYP0553.\n
Contents: Control document. - Level 2. - Level 3. - Levels 4 & 5.